Performance of two neutral oral contrast agents in CT enterography. Issue 1 (27th October 2014) - Wong, Jessica; Roger, Mark; Moore, Helen
Abstract Introduction This study compares the performance of two neutral oral contrast agents in CT enterography (CTE). Mannitol 2.5%, an oral osmotic agent, is compared with psyllium fibre (Metamucil). Both these agents are commonly used, but to our knowledge, they have not been compared in CTE. Methods CTE data were collected from 25 consecutive studies for both mannitol and psyllium fibre between 2011 and 2013. All images were reviewed by two radiologists and one registrar blinded to the oral contrast used. Each quadrant was assessed for maximum distension, proportion of bowel loops distended, presence of inhomogeneous content and bowel wall visibility. Overall subjective quality and whether the contrast agent reached the caecum were also assessed. Patients were invited to answer a questionnaire regarding tolerability of the preparations. Results Wall visibility was rated good in 100% of the mannitol studies, compared with 71% of the psyllium fibre studies, in the right lower quadrant (P = 0.01). No statistically significant difference between groups was observed in either maximal distension or proportion of loops distended in any quadrant. Inhomogeneous material was observed in 12% of the mannitol cases and 86% of the psyllium fibre cases (P < 0.0001). In all mannitol cases, the contrast reached the caecum, compared with 50% of psyllium fibre cases (P < 0.0001), and 36% of the mannitol studies were considered excellent, compared with 20% of the psyllium fibre studies (P = 0.03). Conclusion Mannitol achieves studies of better quality and is now the preferred oral contrast for CTE studies at Auckland City Hospital.